Investigating Oral Cancer Awareness in Outpatient Settings: A Hospital-Based Study (Bangladesh Journal of Medical Science, 2025)
Aim The objective of the study was to evaluate the awareness of the incidence, prevalence, etiology, treatment, prognosis and clinical manifestations of oral cancer among a hospital based out-patient population. A questionnaire with structured questions was prepared and distributed among patients to obtain the information. The questions were designed to determine the level of knowledge about the incidence, prevalence, etiology, treatment, prognosis and clinical manifestations of oral cancer. Method The study, involving 446 participants, revealed a balanced gender distribution (57.3% males, 42.5% females) with diverse age and education profiles. Oral cancer awareness stood at 74.2%, showcasing variations by age and education. Notably, 66.4% believed oral cancer is preventable, highlighting knowledge gaps and emphasizing the need for targeted awareness campaigns in Pakistan. Result The study indicates a noteworthy 75% awareness level among the Multan population regarding oral cancer and its associated risk factors. Conclusion Nevertheless, targeted oral health education is warranted for the remaining 25% to further enhance knowledge and promote health-conscious behaviors in the community.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 450-456